Estudo das catelicidinas no plasma seminal de garanhões e das interleucinas na resposta inflamatória pós-iseminação artificial em éguas - Fioratti, Eduardo Gorzoni [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In the equine species, uterine interleukin expression and seminal plasma cathelicidins can modulate the magnitude and persistence of the post-breeding inflammatory reaction. The objectives were to verify the presence of cathelicidins in the stallion seminal plasma and characterize the uterine immune response by pro and anti-inflammatory interleukins. Seminal plasma was obtained by semen collection of 15 stallions and submitted to SDS-PAGE and DOT-blotting tests. Three experiments were designed to study interleukin expression during baseline (T1), after seminal plasma infusion (T2) and artificial insemination (T3). Endometrial cytology and cell collection as well as ultrassonographic evaluations were performed to access interleukin mRNA through qPCR during three randomly assigned consecutive estrous cycles, 24 (M1), 48 (M2) and 72 hours (M3) after an ovulation was induced. Endometrial mRNA expression in mares resistant and susceptible to persistent post-breeding endometritis was identified for the following pro-inflammatory cytokines: IL-1β, IL-6, IL-8, IL-10 e TNF-α. Total seminal plasma protein concentrations ranged from 6.3 to 25.6 mg/mL. SDS-PAGE analysis identified the existence of three proteic bands with molecular weight similar to what was previously reported for equine cathelicidins. Evaluated stallions showed values < 339.6 ng for eCATH1, < 141.3 ng for eCATH2 and < 283.4 for eCATH3. At M2, resistant and susceptible mares could not be separated through cytology or ultrassonography, even though the presence of sperm strongly stimulates uterine inflammatory reaction. At M3, susceptible mares showed higher uterine fluid accumulation and lower uterine clearance. Pró-inflammatory mRNA expression was higher in susceptible mares and interleukin-10 mRNA expression was similar between resistant and susceptible mares

A expressão das interleucinas no útero e das catelicidinas no plasma seminal podem ser responsáveis pela magnitude e persistência da resposta inflamatória uterina. Os objetivos desse estudo foram verificar a presença das catelicidinas no plasma seminal e caracterizar a resposta imune uterina pela expressão de interleucinas inflamatórias. O plasma seminal foi obtido por coleta de sêmen de 15 garanhões e submetido ao SDSPAGE e DOT-blotting. As éguas foram submetidas a um ciclo estral sem desafio uterino (T1), com infusão de plasma seminal (T2) e inseminação artificial (T3). Exame ultrassonográfico, citologia exfoliativa uterina e colheita de células para a expressão do RNAm das interleucinas por qPCR foram realizados durante 3 ciclos consecutivos aleatoriamente, 24 (M1), 48 (M2) e 72 horas (M3) após a indução da ovulação. A expressão do RNAm no endométrio das éguas resistentes e susceptíveis foi verificada para as interleucinas IL-1β, IL-6, IL-8, IL-10 e TNF-α. A concentração total de proteínas no plasma seminal dos garanhões variou de 6,3 a 25,6 mg/mL. O SDS-PAGE revelou a existência de 3 bandas protéicas dentro do intervalo de peso molecular previamente citado na literatura para as catelicidinas equinas. Os garanhões avaliados mostraram quantidades de eCATH1 < 339,6ng, eCATH2 < 141,3ng e eCATH3 < 283,4ng. No momento M2 não foi possível diferenciar as éguas resistentes das susceptíveis pela citologia ou ultrassonografia independente da infusão com plasma seminal, inseminação artificial ou da ovulação, mas quando há presença de espermatozoides no útero a resposta inflamatória é mais intensa. Durante o momento M3, as éguas susceptíveis apresentaram maior volume de fluido uterino acumulado em todos os tratamentos com menor capacidade de limpeza uterina. Foi verificada maior expressão do RNAm das interleucinas pró-inflamatórias nas éguas susceptíveis e a expressão do RNAm da interleucina-10 é...
Keywords: Equino - Doenças; Egua - Inseminação artificial; Utero - Inflamação; Endometrio - Inflamação; Endometrium